The Research of Infrared Thermal Image Diagnostic Model for Building External Wall Tiles - Chiang, Li-Wei; Guo, Sy-Jye (Advances in Technology Innovation, 2017)
This study focuses on a deterioration diagnostic standard and inspection time for external wall tiles. The study was carried out using a tap tone test, followed by fast Fourier transform and pattern recognition to analyse the tapping results. Based on the test results, the study recommends that for frequencies between 200 and 800 Hz on the spectrogram, it can be deduced that a cavity is present in the tiles. The study was carried out using infrared thermal imaging record to deterioration and normal tile position. This study observed temperature changes per hour, it is obvious temperature difference with deterioration tiles and normal tiles between 09: 00-11: 00 (East), 10:00-14:00 (West), 10:00-12:00 (South) and 11:00-13:00 (North), the study was calculated that the average temperature difference of 1.0 degrees. This study suggests that the best experimental inspection time is 09: 00-14:00. Exclude the impact of external factors, if the temperature difference more than 1.0 degrees, it can be deduced that a cavity is present in the tiles, and this can be used as basis for determining tile deterioration.